Microrheology - Furst, Eric M.; Squires, Todd M. (Oxford University Press, 2017)
Rheology is the study of the flow of matter. It is an important and active field of research that spans numerous disciplines and technological applications. The aim of this work is to provide an introduction to the theory and practice of microrheology, a relatively new area of rheology.